Problematika Manajemen Pendidik dan Tenaga Kependidikan: Studi Literatur Tentang Peningkatan Mutu Pendidikan di Indonesia - Sriyantini Sriyantini; Siti Maisaroh (Indonesian Journal of Islamic Educational Management, 2025)
Education in Indonesia has undergone changes. The current development and progress of the world of education are in line with the needs of the industrial revolution 4.0 by aligning creative and innovative humans and technology. This study aims to analyze the problems of educator and education personnel management towards improving the quality of education in Indonesia. The method used is a qualitative descriptive approach with a literature study and document analysis approach. The literature study and document analysis approach are used to collect data from existing sources, without conducting direct observation. The data collection technique used in this study is to collect data or materials from relevant sources such as books, articles, archives, journals and other written materials related to the problem under study using the Systematic Literature Review (SLR) approach with a systematic review type. The results of the study indicate that the problems of educator and education personnel management indicate the need to strengthen a more integrated and quality-based national policy. The government, in collaboration with the Ministry of Education, Culture, Research, and Technology, needs to strengthen planning for teacher and education personnel needs based on up-to-date national data, by utilizing the education information system to ensure equitable distribution of teachers and education personnel according to the actual needs of educational units, especially in the 3T regions. The importance of leadership in human resource management requires further empirical-based research to strengthen findings and policy recommendations. Further research can be directed at examining the influence of teacher and education personnel management on the quality of learning and student learning outcomes.